Metallosomes for biomedical applications by mixing molybdenum carbonyl metallosurfactants and phospholipids. Issue 40 (28th June 2018) - Marín-García, M.; Benseny-Cases, N.; Camacho, M.; Perrie, Y.; Suades, J.; Barnadas-Rodríguez, R.
Abstract : New photo-CORM metallosomes with low cell toxicity were prepared from organometallic metallosurfactants and phospholipids. Abstract : New supramolecular systems have been prepared by mixing molybdenum organometallic metallosurfactants M(CO)5 L and M(CO)4 L2 L = Ph2 P(CH2 )6 SO3 Na with the phospholipid phosphatidylcholine. The analysis of the resulting supramolecular structures using dynamic light scattering and cryo-transmission electron microscopy has shown the formation of different aggregates depending on the metallosurfactant/phospholipid ratio, as well as a significantly different behaviour between the two studied metallosurfactants. Mixed vesicles, with properties very similar to liposomes, can be obtained with both compounds, and are called metallosomes. The formation of the mixed aggregates has also been studied by microfluidics using MeOH and EtOH as organic solvents, and it has been observed that the size of the aggregates is strongly dependent on the organic solvent used. In order to analyse the viability of these mixed systems as CO Releasing Molecules (CORMs) for biomedical applications, the CO release was studied by FT-IR spectroscopy, showing that they behave as photo-CORMs with visible and ultraviolet light. Toxicity studies of the different mixed aggregate systems have shown that metallosomes exhibit a very low toxicity, similar to liposomes that do not contain metallosurfactants, which is well below the results observed for pure metallosurfactants. Micro-FTIR microscopy using synchrotron radiation has shown the presence of metallosurfactants in cells. The results of this study show the influence of the length of the hydrocarbon chain on the properties of these mixed systems, compared with previously reported data.